Profilin 1 knockdown prevents ischemic brain damage by promoting M2 microglial polarization associated with the RhoA/ROCK pathway. Issue 6 (14th April 2020) - Lu, Ermei; Wang, Qian; Li, Shengcun; Chen, Caiming; Wu, Weibo; Xu, Yang Xin Zi; Zhou, Peng; Tu, Wenzhan; Lou, Xinfa; Rao, Gaofeng; Yang, Guanhu; Jiang, Songhe; et al.
Abstract: Microglial polarization to the anti‐inflammatory M2 phenotype is essential in resolving neuroinflammation, making it a promising therapeutic strategy for stroke intervention. The actin cytoskeleton is known to be important for the physiological functions of microglia, including migration and phagocytosis. Profilin 1 (PFN1), an actin‐binding protein, is involved in the dynamic transformation and reorganization of actin. However, the role of PFN1 in microglial polarization and ischemia/reperfusion injury is unclear. The role of PFN1 on microglial polarization was examined in vitro in BV2 microglial cells subjected to oxygen‐glucose deprivation/reoxygenation (OGDR) and in vivo in male mice after transient middle cerebral artery occlusion (MCAO). Knockdown of PFN1 inhibited M1 microglial polarization and promoted M2 microglia polarization 48 hr after OGDR stimulation in BV2 cells and 7 days after MCAO‐induced injury in male mice. RhoA/ROCK pathway was involved in the regulation of PFN1 during microglial polarization. Knockdown of PFN1 also significantly attenuated brain infarcts and edema, improved cerebral blood flow and neurological deficits in MCAO‐injured mice. Inhibition of PFN1 effectively protected the brain against ischemia/reperfusion injuries by promoting M2 microglial polarization in vitro and in vivo . Abstract : Potential molecular mechanism by which pfn1 regulates microglia polarization and hypoxia/ischemia injuries.